Kelompok Sadar Wisata sebagai Motor Penggerak Pariwisata Berbasis Masyarakat - Hasbiyadi Hasbiyadi; Abd. Mansyur Mus; Zulfikry Sukarno; Ansir Launtu; Ahmad Anto; Lusiana Kanji; Mursida Abu (Transformasi Masyarakat : Jurnal Inovasi Sosial dan Pengabdian, 2025)
Sanrobone Village in Takalar Regency has promising coastal tourism potential, such as mangrove forests, traditional ponds, and local maritime culture. However, this potential has not been optimally managed by the local community. This community service activity aims to increase the capacity of the Tourism Awareness Group (Pokdarwis) as a driving force for community-based tourism development. The implementation method includes field observation, destination management training, digital promotional content creation workshops, assistance in preparing integrated tour packages, and activity evaluation. The results of the activity showed an increase in Pokdarwis' understanding and skills in managing tourist destinations, promoting local potential through social media, and preparing attractive local wisdom-based tour packages. In addition, this activity also succeeded in encouraging synergy between Pokdarwis, the village government, and MSME actors in developing village tourism. This community service activity is expected to be a model for sustainable community-based tourism development in other coastal areas, while contributing to achieving sustainable development goals (SDGs) in the tourism sector.